THE INFLUENCE OF LIQUIDITY, CAPITAL STRUCTURE, PROFITABILITY AND CASH FLOWS ON THE COMPANY’S FINANCIAL DISTRESS - MUHAMMAD REZA FAHLEVI; AAN MARLINAH (Jurnal Bisnis dan Akuntansi, 2018)
Financial distress is a complicated phase and multidimensional problem facing by the company. Since it leads the company on the possibility of bankruptcy, this situation needs immediately to be recovered. This study aims to determine the factors that influence the company's financial distress. There are ten variables in this study which are classified into four categories: liquidity, capital structure, profitability and cash flows. This study used financial statement data of manufacturing company which is listed in Indonesia Stock Exchange during the threeyear study period from 2011 to 2013. There are some criteria in choosing the representative sample so that the sum of the companies are 90 companies or equal to 270 financial statements data. The empirical findings show that there are only three variables that influence the company’s financial distress. The significant variables are current ratio (liquidity), return on assets (profitability) and cash flow ratio (cash flow).